ChemInform Abstract: Manganese‐Catalyzed Borylation of Unactivated Alkyl Chlorides. Issue 46 (October 2016) - Atack, Thomas C.; Cook, Silas P.
Abstract: A mild and convenient synthesis of alkyl bispinacolato esters is developed using primary, secondary and even tertiary alkyl halides in the presence of MnBr2 and TMEDA as low cost catalysts.